Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Algebra 2 help again pleeeasee?
ive been working on it for forever, and ive always gotten 4 but thats not one of the answers. Problem: √4t-7=-3 ( 4t and 7 under radical)
This one also: √5x-7=√3x+3 (all under radical.)
The first one is actually √4t-7 +4=-3 with 4 not under the radical
6 Answers
- mr. coolLv 58 years agoFavorite Answer
√(4t - 7) + 4 = -3
√(4t - 7) = -7
4t - 7 = 49
4t = 56
t = 14
However, plugging in 14 for t gives a false statement. The extraneous solution is 14.
√(5x - 7) = √(3x + 3)
5x - 7 = 3x + 3
5x = 3x + 10
2x = 10
x = 5
- ?Lv 68 years ago
√(4t - 7 ) + 4 = -3
√(4t - 7 ) = -7
4t - 7 = 49
4t = 56
t = 8 which doesn't check. empty set
5x-7=3x+3 so 2x =10
x = 5 which checks
- ?Lv 48 years ago
First one, square everything and the 4 outside.
Leaves you with this: 4t-7 +16=9
Second one should have this after squaring both sides: 5x-7=3x+3 ----- 2x-7=3 ---- Solve for x
- ?Lv 78 years ago
if you can isolate the radical as a single term on one side of the equation
you can square both sides
sqrt(4t-7)= -3
square both sides
4t-7=9
4t=16
t=4
sqrt(5x-7)=sqrt(3x+3)
square both sides
5x-7=3x+3
2x=10
x=5
oops
first one
sqrt(4t-7)+4= -3
sqrt(4t-7)= -7
square both sides
4t-7= 49
4t=56
t=+/-sqrt(56)=+/-2sqrt(14)
- How do you think about the answers? You can sign in to vote the answer.
- ErikaLv 45 years ago
a million - (4/(x+6)) = 4/x rewrite first component as: (x+6)/(x+6) - (4/(x+6)) which would be decreased to: (x + 2)/(x+6) you're able to come across a undemanding denom. between the two: multiply the left component via (x/x) and the main appropriate component via (x+6/x+6) this will supply you: (x^2+2x)/(x^2+6x) = (4x + 24)(x^2+6x) B/c the denom. are comparable they are able to be omitted, giving: x^2 + 2x = 4x + 24 which would be written as: x^2 - 2x - 24 = 0 that's: (x - 6)(x+4) = 0 hence x = 6 or -4 rewrite